Between a Rock and a Hard Place: Teaching International Law in Sri Lanka - Medawatte, Danushka (Afronomics Law, 2020)
This post explores the challenges of teaching International Law (IL) in Sri Lanka with reference to biases arising from dominant narratives, issues pertaining to study materials and teacher training, divisions caused by language, and the global ‘North-South’ dynamics.
This post is one part of a series of short articles authored by TWAIL Scholars from all over the world for a symposium entitled "Teaching and Researching International Law: Global Perspectives".
Keywords: International Law; Pedagogy; Teaching; Public International Law; TWAIL; Third World Approaches to International Law; Subaltern; Global North and Global South